Unveiling Gender Differences in Adolescent Coping: Insights from High School Students in Jakarta - Charli Sitinjak; Ellya Rakhmawati; Ummu Hany Almasitoh; Anna Febrianty (Universitas Muhammadiyah Surakarta, 2024)
Adolescence is a crucial developmental stage characterized by various challanges that require effective coping techniques. This study examines gender differences in adolescent girls' and boys' cognitive-emotional coping methods. Conducted on 130 high school students in Jakarta, Indonesia, the research utilized the Cognitive Emotion Regulation Questionnaire (CERQ) and SPSS 20 for analysis.The findings reveal significant gender-specific differences in coping strategies. Female students predominantly employ maladaptive coping strategies, scoring higher in Catastrophizing (Mean = 14.2, SD = 3.1) and Rumination (Mean = 15.6, SD = 3.5) compared to their male counterparts (Catastrophizing: Mean = 12.3, SD = 3.4; Rumination: Mean = 13.2, SD = 3.2). In Contrast, male students exhibita more balanced use of adaptive and maladaptive strategies, with higher scores in strategies like Positive Reappraisal (Mean = 16.4, SD = 3.2) compared to females (Mean = 14.8, SD = 3.0). These gender-specific differences highlight the need for tailored interventions and educational programs that address the unique coping needs of each gender. Furthermore, this study contributes novel insights into the cognitive-emotional coping landscape within Southeast Asia, a region with limited existing research. By understanding these gender-specific coping strategies, educators, parents, and mental health professionals can better support adolescents in developing healthier coping mechanisms, ultimately enhancing their psychological resilience and well-being. This research lays the groundwork for future studies and practical applications aimed at improving adolescent mental health through targeted coping strategy interventions.